Structural Impacts of Global Climate Agreements on CO2 Emissions and Economic Growth in 106 Middle-Income Countries - Al Mamun, Tuhin G. M.; Ehsanullah, Ehsanullah; Bin Amin, Mohammad; Fenyves, Veronika; Oláh , Judit (International Journal of Energy Economics and Policy, 2025)
Rising CO2 emissions remain a critical challenge for middle-income countries, where economic growth continues to drive environmental degradation. This study examines the long- and short-run relationships between CO2 emissions, energy use, GDP per capita, and population in 106 middle-income countries from 1980 to 2023. Using a Panel Vector Error Correction Model (VECM) with structural breaks for the UNFCCC (1994), Kyoto Protocol (2005), and Paris Agreement (2016), it evaluates the comparative effectiveness of major international climate agreements. Cointegration tests confirm a stable long-run equilibrium among the variables, with GDP per capita exerting upward pressure on emissions, while rising energy use increasingly reflects efficiency gains and cleaner technologies. The results show that the Kyoto Protocol produced a modest but statistically significant reduction in emissions, while the UNFCCC had a smaller yet meaningful influence. By contrast, the Paris Agreement has not yet delivered measurable long-run or short-run impacts. Granger causality tests confirm that energy use strongly drives emissions in the short run, while GDP per capita and population exert gradual effects over time. Variance decomposition and impulse response analysis further demonstrate that emissions trajectories remain shaped more by energy and economic dynamics than by participation in global agreements. Robustness checks, including autocorrelation diagnostics and slope homogeneity tests, confirm model stability. The findings highlight that while binding commitments under Kyoto generated observable though limited progress, voluntary frameworks such as Paris remain insufficient without strong domestic policy enforcement, sector-specific reforms, and sustained investment in renewable energy.